The Effect of Work System and Workplace Hazards on Employeeas Behaviour (Global Journal of Management and Business Research, 2014)
Information and Communication Technology (ICT) stands out as a major driver of the modern age. It espousal in virtually every sector of the economy led to a paradigm shift from conventional way of work arrangement to a new form of work system, workplace hazards as well as employee's behavior across the globe. This study examined the effect of work system and workplace hazards on employee's behaviour. It aimed at addressing the issue of how work can be structured in order to reduce workplace hazards and produce affirmative employee's work behavior. The study adopted survey research method. Participants in the study were 120 staffs of Nigerian Eagle Flourmill, Ibadan who were selected through stratified and simple random sampling techniques. Data were collected via responses elicited using the questionnaire instrument. Results show that there is a significant relationship between work system, workplace hazards and employees behaviour. The findings were discussed with reference to relevant empirical literatures, and with recommendations for management of organizations both for practice and future research highlighted.
Keywords: work system; workplace hazard; employees; behaviour; organization